Micro, macro, and strategic forces in international trade invoicing - Linda S. Goldberg; Cédric Tille (Federal Reserve Bank of New York, 2009)
The use of different currencies in the invoicing of international trade transactions plays a major role in the international transmission of economic fluctuations. Existing studies argue that an exporter's invoicing choice reflects structural aspects of its industry, such as market share and the price sensitivity of demand, as well as the hedging of marginal costs (due, for instance, to the use of imported inputs) and macroeconomic volatility. We use a new, highly disaggregated data set to assess the roles of the various invoicing determinants. Our findings support the factors identified in the literature and document a new feature: a link between shipment size and invoicing. Specifically, larger transactions are more likely to be invoiced in the importer's currency. We offer a theoretical explanation for the empirical link between transaction size and invoicing by allowing invoicing to be set through bargaining between exporters and importers, a feature absent from existing models despite its empirical relevance.
Keywords: F3; F4; 330; Invoicing currency; vehicle currency; pass-through; international trade; Außenwirtschaft; Internationale Handelspolitik; Transaktionskosten; Internationaler Zahlungsverkehr; Währung; Welt